(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
Calcareous foraminifers provide a time-stratigraphic framework to chronicle the development of the Tengiz carbonate platform that thrived from the latest Devonian (late Famennian) into the Middle Pennsylvanian (late Bashkirian). Correlative zones, based on documented foraminiferal assemblages and expressed primarily in terms of Russian horizons, confirm that the platform grew in a complex pattern of progradation and backstepping from the Tournaisian to late Visean and then underwent a major progradation that was terminated by sea level fall at the end of the Serpukhovian. Favorable conditions for carbonate sedimentation returned in the early Bashkirian and persisted into the late Bashkirian until the platform either was exposed and eroded or buried by siliciclastic deposition. Breaks in the foraminiferal succession point to major depositional hiatuses along the top of the Bashkirian platform, at the Mississippian-Pennsylvanian boundary, and possibly in the late Tournaisian although previous investigations support continuous deposition throughout the latter interval at Tengiz.